TRAGIC LOSS OR GOOD RIDDANCE? THE IMPENDING DEMISE OF TRADITIONAL SCHOLARLY JOURNALS - Odlyzko, Andrew (Surfaces, 1994)
Refering particuliarly to mathematics and the natural sciences, the author argues that the potential of electronic technology renders traditional publishing superfluous.